2018
DOI: 10.3389/fphys.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

Structural Immaturity of Human iPSC-Derived Cardiomyocytes: In Silico Investigation of Effects on Function and Disease Modeling

Abstract: Background: Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have emerged as a promising experimental tool for translational heart research and drug development. However, their usability as a human adult cardiomyocyte model is limited by their functional immaturity. Our aim is to analyse quantitatively those characteristics and how they differ from adult CMs.Methods and Results: We have developed a novel in silico model with all essential functional electrophysiology and calcium handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
127
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 58 publications
(117 reference statements)
1
127
0
1
Order By: Relevance
“…Before the upstroke, the new I NCX provides an additional inward contribution (−0.5A/F) that is added to If (−0.25A/F), supporting the membrane depolarization and allowing the opening of the I Na channels. Figure 1 illustrates the contribution of I NCX to the hiPS-CM automaticity, as reported in (16, 33): blocking I NCX reduces its inward component slowing down the rate of spontaneous AP, up to suppression. In particular, an issue in the Paci2018 model was that AP suppression did not happen, in disagreement with in vitro data by Kim et al (33) in response to 2μM SEA0400, an inhibitor of the forward I NCX in a cluster of hiPS-CMs.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…Before the upstroke, the new I NCX provides an additional inward contribution (−0.5A/F) that is added to If (−0.25A/F), supporting the membrane depolarization and allowing the opening of the I Na channels. Figure 1 illustrates the contribution of I NCX to the hiPS-CM automaticity, as reported in (16, 33): blocking I NCX reduces its inward component slowing down the rate of spontaneous AP, up to suppression. In particular, an issue in the Paci2018 model was that AP suppression did not happen, in disagreement with in vitro data by Kim et al (33) in response to 2μM SEA0400, an inhibitor of the forward I NCX in a cluster of hiPS-CMs.…”
Section: Resultsmentioning
confidence: 78%
“…Research on hiPS-CMs is rapidly developing, with new experimental data becoming available, which in turn serve as a driving force for the constantly evolving computational models to offer more accurate in silico tools to the scientific community. Based on in vitro (33) and in silico (16) tests, it was identified that our Paci2018 hiPS-CM model (15) did not properly reflect the role of I NCX in automaticity, i.e. no cessation of spontaneous activity was seen in the model as consequence of a strong I NCX block, as suggested by experiments.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations